Digital (r)evolution in the context of primary school education – the attiudes of the teachers and students of teacher education and pedagogy faculties - Purić, Daliborka; Kostić, Ljiljana; Marinković, Snežana (Sociološki pregled, 2023)
Revolutionary development of the global communication network has also been reflected on the electronic book as the most important product of digitalization, and a significant educational resource in the function of providing a stimulating learning environment. The authors examine teachers’ experiences (N=1117) (a) in relation to the justification of using electronic books and the attitudes of teachers and students of teacher education and pedagogy faculties (N=214) in relation to (b) the perspective of using different formats of books and (c) the universal values of the book, regardless of the format in which it was published. The research results show that teachers’ motivation for using electronic books in teaching is mostly intrinsic; that teachers and future teachers agree in their attitudes regarding the use of electronic and printed books in the context of text media future development, as well as in their attitudes related to the universal values of the book in general, regardless of advantages and disadvantages of the format in which it was designed. The developed critical attitude of teachers and future teachers towards the potential of technological development of the book in the function of active knowledge building is significant from the aspect of the functionality of modern media in the educational context, bearing in mind that the key role in designing the learning process with the use of modern technology actually belongs to the teacher.